Perceptions of female offenders / volume 2 - Russell, Brenda; Torres, Celia (Perceptions of female offenders how stereotypes and social norms affect criminal justice responses, 2023)
This new edition is a nuanced exploration of female involvement in various crimes-from delinquency, domestic violence, sexual assault and homicide-that resonates with the pulse of contemporary society. In an age where many events are tweeted and debated online, this book delves into the intricate ways social media portrays female offenders and how this can distort public perceptions and effect legal outcomes. Volume two includes recent research and theory examining how female perpetration is intricately related to gender roles that persist within the criminal justice system and often lead to gender disparities in treatment, criminal justice response, and sentencing and calls into question long-held beliefs and systems that might not be as impartial as they appear. The compelling nature of this volume addresses the complex relationship between trauma and offending and examines crucial subjects like partner violence homicide and the unique challenges faced by trans-women within the criminal justice system, and examines the myths associated with female offending and how that bleeds into criminal justice response. It addresses theories that provide insight into female offending and sentencing and offers ways to generate gender inclusiveness. This volume invites researchers, practitioners, and advocates for justice to join a vital conversation and develop a more informed and equitable criminal justice response